A8.03 Differential methylation as a biomarker of response to etanercept in patients with rheumatoid arthritis. (24th February 2016) - Plant, D; Webster, A; Nair, N; Oliver, J; Smith, S; Eyre, S; Hyrich, KL; Wilson, AG; Morgan, AW; Isaacs, J; Worthington, J; Barton, A
Abstract : Background: Biologic drug therapies represent a huge advance in the treatment of rheumatoid arthritis (RA). However, very good disease control is only achieved in 30% of patients, making identification of biomarkers of response a research priority. We therefore hypothesise that differential DNA methylation patterns may provide biomarkers predictive of response to TNF-inhibitor (TNFi) therapy in patients with RA. Methods: An epigenome-wide association study was performed on pre-treatment whole blood DNA from patients with RA. Patients who displayed good response (n = 36) or no response (n = 36) to etanercept therapy at 3-months were selected. Differentially methylated positions (DMPs) were identified using linear regression. Variance of methylation at DMPs was assessed for correlation with cis- acting SNPs. A replication experiment for prioritised SNPs was performed in an independent cohort of 1, 204 RA patients. Results: Five DMPs between responders groups were identified with a FDR <5%. The top two DMPs mapped to exon 7 of the LRPAP1 gene on chromosome 4 (cg04857395, p = 1.39E-08 and cg26401028, 1.96E-08). The A allele of the SNP rs3468 was correlated with higher levels of methylation for both of the top two DMPs (2.63E-07 and 1.05E-06, respectively). Further the A allele of rs3468 was correlated with EULAR non-response in the discovery cohort (n = 56; p = 0.03) and in the independent replication cohort (n = 1.204; p = 0.003). Conclusions: We identify DNA methylation as a potential biomarker of TNFi response and report the association between response and the LRPAP1 gene which encodes a chaperone of low-density lipoprotein receptor-related protein-1. Additional replication experiments in independent sample collections are now required.